Mindful muscles: an innovative education project to tackle doping use in recreational sport and fitness - Tavares, Ana Sofia (2023)
Background: Athletes in recreational sports do not receive the same attention and have far more limited access to learning resources when it comes to anti-doping education, as compared to athletes in elite, competitive, organized sports. Furthermore, the existing anti-doping education resources for recreational sports athletes are informed by relevant practices in elite/competitive sports and largely focus on a deficit-based educational model that is concerned with fixing athletes' weaknesses or lack of skills. Objectives: Project Mindful Muscles aims to provide recreational sports athletes and related professionals with a novel, strengths-based approach, based on educational resources that are informed by evidence-based interventions on mindfulness, self-compassion, acceptance, and values (MASC), which will enable athletes in recreational sport to effectively cope with situations and pressures that may increase their personal risk for doping. Methods: Systematic literature review and report on best practices of self-administered MASC applications in substance use and body image impairments, to developed MASC resources, followed by a formative evaluation of the Mindful Muscles workbook with 350 exercisers 18-25 years old across seven European countries. Results: The findings supported the development of a framework for developing MASC resources for the primary and secondary prevention of PEDs (4 modules including different types of MASC exercises). The findings also informed the content and approach of the Mindful Muscles intervention and the implications of using strengths-based and positive approaches to doping prevention. Conclusions: The project Mindful Muscles is the first multifaceted, international psycho-educational intervention to tackle doping use among amateur athletes and exercisers, whose resources have the potential to inspire users to improve their lives not just in the sports arena, but also in other important life domains.